Strategies for vitamin B6 biofortification of plants: a dual role as a micronutrient and a stress protectant - Vanderschuren, Hervé; Boycheva, Svetlana; Li, Kuan-Te; Szydlowski, Nicolas; Gruissem, Wilhelm; Fitzpatrick, Teresa B. (Frontiers in Plant Science, 2013)
Vitamin B6 has an essential role in cells as a cofactor for several metabolic enzymes. It has also been shown to function as a potent antioxidant molecule. The recent elucidation of the vitamin B6 biosynthesis pathways in plants provides opportunities for characterizing their importance during developmental processes and exposure to stress. Humans and animals must acquire vitamin B6 with their diet, with plants being a major source, because they cannot biosynthesize it de novo. However, the abundance of the vitamin in the edible portions of the most commonly consumed plants is not sufficient to meet daily requirements. Genetic engineering has proven successful in increasing the vitamin B6 content in the model plant Arabidopsis. The added benefits associated with the enhanced vitamin B6 content, such as higher biomass and resistance to abiotic stress, suggest that increasing this essential micronutrient could be a valuable option to improve the nutritional quality and stress tolerance of crop plants. This review summarizes current achievements in biofortification of vitamin B6 and considers strategies for increasing vitamin B6 levels in crop plants for human health and nutrition.